1971
DOI: 10.1161/01.res.29.6.691
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Forelimb Weight and Segmental Vascular Resistances Following Severe Hemorrhage

Abstract: The forelimb was used to study capillary fluid fluxes following hemorrhage in dogs anesthetized with sodium pentobarbital. Arterial hemorrhage (48 ml/kg) and 4 hours of hypovolemia produced decreases in forelimb weight, arterial and venous pressures, and skin and skeletal muscle blood flows. Segmental resistances (large artery, small vessel, large vein) in both skin and skeletal muscle increased markedly, and the increase was either completely or largely maintained throughout the hypovolemic period. The large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1973
1973
1982
1982

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The latter aspect will first be commented upon. Grega, Schwinghamer & Haddy 1971, Jarhult 1973, Hall, Schwinghamer & Lalone 1976). In most of these studies a fixed hypotension level achieved with the aid of a pressure bottle (Werle, Cosby & Wiggers 1942) has been gsed.…”
Section: Discussionmentioning
confidence: 99%
“…The latter aspect will first be commented upon. Grega, Schwinghamer & Haddy 1971, Jarhult 1973, Hall, Schwinghamer & Lalone 1976). In most of these studies a fixed hypotension level achieved with the aid of a pressure bottle (Werle, Cosby & Wiggers 1942) has been gsed.…”
Section: Discussionmentioning
confidence: 99%
“…These fluid shifts were associated with higher values of hematocrit and blood viscosity in the SpI-D dogs in late oligemia and after retransfusion. The transcapillary fluid loss seen in the SpI-D dogs probably reflects a rise in the postcapillary to precapillary resistance ratio in the limb vessels (8, 26,32,42), and a portion of this fluid loss may occur in the intestine (14, 48). It is interesting to note that, of the four groups studied, pathologic changes in the intestine were most pronounced in the SpI-D dogs ( Table 2).…”
Section: Role Of Spleenmentioning
confidence: 99%
“…In the intact cat paw (Oberg 1964) and dog foreleg (Schwinghamer et al 1970, Grega et al 1971, hemorrhage has been shown to cause a fluid absorption, which was attributed to adrenergic resetting of the pre-to postcapillary resistance ratio.…”
Section: Discussionmentioning
confidence: 99%